Gulo Puan Visual Brand: Medium Promotion of Gastronomic Tourism Destinations, Pampangan District, South Sumatra - Sumbo Tinarbuko; Risvi Pangestu; I Wayan Nuriarta (Institut Seni Indonesia Denpasar, 2023)
Gulo Puan is a traditional food from the Pampangan sub-district, South Sumatra Province. Its existence has sunk into the ages. Gulo Puan does not yet have a visual brand that can represent her existence. The absence of a visual brand makes people less aware of the existence of this gastronomy. The purpose of this study is to present the Gulo Puan visual brand as a promotional medium for the gastronomic tourism destination